How Should Individual-Level Economic Voting Studies Measure Perceptions? A Meta-Analysis - Arya Budi (Asian Journal for Public Opinion Research, 2024)
The literature on economic voting is vast. One of the primary debates is about how to measure economic performance as the central variable explaining incumbent survival. This paper offers a systematic examination of accumulated knowledge on economic voting and about different operationalizations of the key explanatory variable in individual-level economic voting studies. By investigating studies published in top-ranked journals and meta-analyzing the reported estimates, this paper finds that a sociotropic-retrospective measure, i.e., an individual’s perception of national economic conditions in the recent past, has a higher predictive power than other measures common in studies of economic voting. While a systematic meta-analysis has never been attempted using a large collection of works on individual-level economic voting studies, the findings also give us a strong reason to use sociotropic evaluation rather than pocketbook evaluation and more utilization of retrospective judgment than prospective. These other methods are also examined in the current article. This finding should help researchers choose measurement strategies in future studies.